KEBIJAKAN RESTRUKTURISASI KREDIT SELAMA MASA PANDEMI COVID-19 (Studi Kasus Di Bank BTN Ciputat) - Cahya Zenitha (2022)
The spread of Covid-19 has forced many business sectors to limit their business activities, including the banking sector which has to face an increase in non-performing loans. The problems posed are how are the obstacles to implementing credit restructuring at Bank BTN Ciputat during the Covid-19 pandemic, and how should the implementation of credit restructuring at banks during the Covid-19 pandemic provide justice for debtors and creditors. The research method used is normative juridical which is supported by primary data in the form of interviews. The results of the study show that the obstacles faced in implementing credit restructuring at Bank BTN Ciputat are that many parties take advantage of the Covid-19 pandemic situation to restructure loans such as civil servants, TNI, and POLRI. In addition, many debtors filed complaints because after the credit restructuring period, there was an extension of the credit period. The implementation of credit restructuring in banks during the Covid-19 pandemic that can provide justice for debtors and creditors is implemented based on POJK Number 48 / POJK.03/2020. The suggestions given are: 1) There must be clear and detailed communication between Bank BTN Ciputat and debtors regarding credit restructuring; 2) the implementation of credit restructuring must be carried out with full responsibility and prioritizing good faith from creditors and debtors. Keywords: Credit Restructuring, The Covid-19 Pandemic